Auditoría de cumplimiento de las normas tributarias vigente en la gestión contable del comercial Mercedes de la parroquia San Carlos del cantón Quevedo, año 2011 - Alcivar Molina, Betty Carolina (2013)
This research project is entitled Audit of Compliance with tax regulations in Mercedes Commercial Management Accountant of the Parish of San Carlos Quevedo Canton 2011. The project's theme was chosen by the business necessity of an evaluation of compliance with tax regulations and according to the results take steps to avoid fines and penalties from the Internal Revenue Service. With the implementation of the audit findings were detected and provided specific recommendations to the owner, the project contains the introduction, justification, expected changes; objectives, assumptions, theoretical framework, the research results detailing the audit process with their respective working papers, we applied the respective audit procedures such as observation, interviews, surveys, inspections were carried out, calculations, reviewing statements and the corresponding receipts sales and retention, reporting, comparisons, and ending this chapter with the report audit detailing the findings detected in non-compliance with tax regulations, and recommendations specifically the accounting area, conclusions and recommendations of the project, the bibliography and appendices.